Penggunanan Media Kartu Huruf A-Z untuk Meninglkatkan Kemampuan Mengenal Huruf Anak Tunagrahti Ringan Kelas VII di SLB Negeri Manekat Niki-Niki - Silla, Yermia; Selan, Ot Bill Wilson; Wangge, Vinsensius; Sene, Chamelya Vivi Crystanty; Lodo, Rozita Yusniaty; Ajito, Timoteus (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to improve the ability of students with mild intellectual disabilities to recognise the letters A–Z through the use of letter cards as a visual aid in early reading instruction. The study used a classroom action research (CAR) design, which was carried out in two cycles, each comprising the stages of planning, implementation of actions, observation, and reflection. The research subjects consisted of three students with mild intellectual disabilities in Grade VII at SLB Negeri Manekat Niki-Niki. Data were collected through observation, performance tests, and documentation of learning activities, then analysed descriptively, qualitatively, and quantitatively by comparing the results of the pre-action, cycle I, and cycle II. The results showed a clear improvement in letter recognition skills in all subjects after using the A–Z letter card media, as seen from the increase in scores at each stage of action. These findings show that letter card media effectively help students recognise letter shapes more accurately and consistently, and can be applied as an alternative learning strategy that supports the development of early reading skills for students with mild intellectual disabilities at special needs schools.